IMPLEMENTASI BAHAN AJAR BERBASIS INQUIRY LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTS - Mayang; Nirfayanti; Ernawati (Jurnal Penalaran dan Riset Matematika, 2024)
This study uses a quasi-experimental method that aims to determine the improvement of mathematical communication skills of 8th grade students of MTs Al Irsyad Biringkaloro before and after the application of mathematics teaching materials based on the Inquiry Learning model. This study used an initial test (pretest) and final test (posttest) to compare students' abilities before and after learning. The research sample was taken purposively from class VIII-A. The research data were obtained through a test specifically designed to measure students' ability to communicate mathematically, and this test has been assessed as valid by experts. The data obtained were analyzed using descriptive statistics to describe the data in general, and inferential statistics (independent sample t-test) to test for significant differences between pretest and posttest scores. The results showed an increase in mathematical communication skills where the average value of the pretest was 64.15 with a sufficient category while in the posttest results 77.30 with a high category and the results of the independent sample t-test which showed that there was a positive effect of the Inquiry learning model mathematics teaching materials on the mathematical communication skills of 8th grade students of MTs Al Irsyad Biringkaloro